Volatile multinationals? Evidence from the labor demand of German firms - Claudia M. Buch; Alexander Lipponer (Deutsche Bundesbank, 2007)
Does more FDI make the world a riskier place for workers? We analyze whether an increase in multinational firms' activities is associated with an increase in firm-level employment volatility. We use a firm-level dataset for Germany which allows us to distinguish between purely domestic firms, domestic multinationals, their foreign affiliates, and foreign firms that are active in Germany. We decompose the volatility of firms into their reaction and their exposure to aggregate developments. Generally, we find no above-average wage and output elasticities for multinational firms.
Keywords: J23; F23; 330; Employment volatility; labor demand; multinational firms; Multinationales Unternehmen; Globalisierung; Arbeitsnachfrage; Beschäftigungseffekt; Schätzung; Deutschland